Supplier fairness as a mediating factor in the supplier performance-reseller satisfaction relationship - Yilmaz, C; Sezen, B; Kabadayi, ET (Elsevier Science Inc, 2004)
The study examines the role of reseller perceptions of supplier fairness in the relationships between reseller evaluations of supplier role performance components and reseller satisfaction. Specifically, reseller perceptions of supplier distributive fairness and procedural fairness are posited as key factors, mediating the effects of reseller assessments of supplier delivery performance, operational support, boundary personnel performance, and financial and sales performance on reseller satisfaction. Results of nested model comparisons using data collected from resellers in Turkey support the hypothesized mediating role of fairness perceptions. Specific relationships between supplier performance components and fairness perceptions, as well as the effects of both fairness types on reseller satisfaction, are discussed. (C) 2002 Elsevier Inc. All rights reserved.
Keywords: supplier fairness; supplier performance; reseller satisfaction